Imaging Expression of Cytosine Deaminase-Herpes Virus Thymidine Kinase Fusion Gene (CD/TK) Expression with [I]FIAU and PET - Trevor Hackman; Michail Doubrovin; Julius Balatoni; Tatiana Beresten; Vladimir Ponomarev; Bradly Beattie; Ronald Finn; William Bornmann; Ronald Blasberg; Juri Gelovani Tjuvajev (Molecular Imaging)
Double prodrug activation gene therapy using the Escherichia coli cytosine deaminase (CD)herpes simplex virus type 1 thymidine kinase ( HSV1-tk ) fusion gene ( CD/TK ) with 5-fluorocytosine (5FC), ganciclovir (GCV), and radiotherapy is currently under evaluation for treatment of different tumors. We assessed the efficacy of noninvasive imaging with [ 124 I]FIAU (2′-fluoro-2′-deoxy-1-β-d-arabinofuranosyl-5-iodo-uracil) and positron emission tomography (PET) for monitoring expression of the CD/TK fusion gene. Walker-256 tumor cells were transduced with a retroviral vector bearing the CD/TK gene (W256CD/TK cells). The activity of HSV1-TK and CD subunits of the CD/TK gene product was assessed in different single cell-derived clones of W256CD/TK cells using the FIAU radiotracer accumulation assay in cells and a CD enzyme assay in cell homogenates, respectively. A linear relationship was observed between the levels of CD and HSV1-tk subunit expression in corresponding clones in vitro over a wide range of CD/TK expression levels. Several clones of W256CD/TK cells with significantly different levels of CD/TK expression were selected and used to produce multiple subcutaneous tumors in rats. PET imaging of HSV1-TK subunit activity with [ 124 I]FIAU was performed on these animals and demonstrated that different levels of CD/TK expression in subcutaneous W256CD/TK tumors can be imaged quantitatively. CD expression in subcutaneous tumor sample homogenates was measured using a CD enzyme assay. A comparison of CD and HSV1-TK subunit enzymatic activity of the CD/TK fusion protein in vivo showed a significant correlation. Knowing this relationship, the parametric images of CD subunit activity were generated. Imaging with [ 124 I]FIAU and PET could provide pre- and posttreatment assessments of CD/TK -based double prodrug activation in clinical gene therapy trials.